Disinvesting in the future? A comprehensive examination of the effects of state appropriations for public higher education - Bo Zhao (Federal Reserve Bank of Boston, 2018)
In aggregate, state appropriations are the largest revenue source for public higher education in the United States. However, these appropriations have significantly declined over past decades, drawing serious concerns about the potential negative impact on schools and students. This paper provides a more comprehensive study of the effects of state appropriations than previous research, while explicitly exploring and testing the heterogeneity of the effects by institutional type. It finds strong evidence of the negative effects of state appropriation cuts in the areas of tuition and fees, student financial aid, instructional and other school expenditures, and degree completion. Community colleges, which serve the most undergraduates but have not been well studied by past research, are shown to be particularly vulnerable to the negative effects of state funding cuts.
Keywords: H2; H4; H7; I2; 330; state appropriations; public higher education; community colleges; state funding cuts